UiTM Sarawak's collaboration - Yeo Jiin Yih, Jacinta (UiTM Sarawak, 2015)
This collaboration enhances UiTM Sarawak’s primary mission, which is education and the advancement of knowledge through information and communication technology. This university always seizes the opportunities to establish strategic collaboration with various agencies to share ideas and enhance the quality of the graduates and research.